Revolutionary and dissident movements of the world - Szajkowski, Bogdan (Gale virtual reference library, 2004)
"Covers the whole range of illegal political activity worldwide, ranging from terrorist and secessionist organizations to dissident groups operating clandestinely in authoritarian states. Resource of more than 5,000 organizations and individuals explains the history and contemporary significance of each organization and the political background against which it operates."--GVRL description.